2021
DOI: 10.1038/s41467-020-20765-1
|View full text |Cite
|
Sign up to set email alerts
|

Conserved regulatory logic at accessible and inaccessible chromatin during the acute inflammatory response in mammals

Abstract: The regulatory elements controlling gene expression during acute inflammation are not fully elucidated. Here we report the identification of a set of NF-κB-bound elements and common chromatin landscapes underlying the acute inflammatory response across cell-types and mammalian species. Using primary vascular endothelial cells (human/mouse/bovine) treated with the pro−inflammatory cytokine, Tumor Necrosis Factor-α, we identify extensive (~30%) conserved orthologous binding of NF-κB to accessible, as well as nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 135 publications
(257 reference statements)
2
43
0
Order By: Relevance
“…A recent study by Alizada et al (2021) offered key insights into the expression dynamics of both these classes of genes that are triggered by NF-kB, a master TF implicated in various inflammatory signaling pathways ( Natoli, 2009 ). Upon its translocation into the nucleus, NF-kB binds to promoters and enhancers of proinflammatory genes to stimulate their transcription ( Pierce et al, 1988 ).…”
Section: Chromatin Structure Modulation and Enhancer-based Regulationmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study by Alizada et al (2021) offered key insights into the expression dynamics of both these classes of genes that are triggered by NF-kB, a master TF implicated in various inflammatory signaling pathways ( Natoli, 2009 ). Upon its translocation into the nucleus, NF-kB binds to promoters and enhancers of proinflammatory genes to stimulate their transcription ( Pierce et al, 1988 ).…”
Section: Chromatin Structure Modulation and Enhancer-based Regulationmentioning
confidence: 99%
“…Intriguingly, NF-kB has also been demonstrated to utilize a third mode of chromatin interaction, by binding to nucleosome-occluded domains in a manner that is reminiscent of pioneer TFs, although its functional importance remains controversial ( Steger and Workman, 1997 ; Angelov et al, 2003 ; Angelov et al, 2004 ; Lone et al, 2013 ; Cieslik and Bekiranov, 2015 ). Through comparative epigenomic investigation of the genome-wide localization dynamics of NF-kB in human, murine and bovine cells stimulated with the proinflammatory cytokine TNFα, Alizada et al (2021) showed a substantial proportion of conserved orthologous NF-kB binding not only to accessible, but also nucleosome-bound chromatin regions. In fact, NF-kB occupancy within the latter context is likely an integral aspect of the NF-kB-induced acute inflammatory response, as reproducible results were obtained with ChIP-seq using different NF-kB subunits in diverse cell types, and these regions were significantly enriched within super-enhancer (SE) domains, which constitute about a third of all NF-kB SE binding peaks ( Alizada et al, 2021 ).…”
Section: Chromatin Structure Modulation and Enhancer-based Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…A robust characterization of the transcriptional and epigenetic regulatory elements that contribute to endothelial dysfunction has remained an important challenge for atherosclerosis research and has been recently addressed with next-generation approaches for global EC profiling. Of note, the integration of chromatin immunoprecipitation, chromatin accessibility, and RNA sequencing has enabled identification of diverse DNA regulatory elements associated with disturbed flow and proinflammatory activation (e.g., NF-κB and hypoxia inducible factor 1α, as well as ETS, zinc finger, and activator protein 1 transcription factor families) ( Hogan et al, 2017 ; Bondareva et al, 2019 ; Alizada et al, 2021 ). Moreover, combined single-cell RNA sequencing and genome-wide chromatin accessibility assays have been used to profile the genome- and epigenome-wide changes associated with proatherogenic ECs under oscillatory shear stress ( Andueza et al, 2020 ).…”
Section: Endothelial Cells Govern Site-specificity Of Atherogenesismentioning
confidence: 99%